Developing BSI Agent Networks to Strengthen Islamic Banking Financial Inclusion: Insights from an Analytic Network Process Study - Ismul Fakhri Lubis; Azhari Akmal Tarigan; Andri Soemitra; Muhammad Rizal; Kaswinata Kaswinata (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines strategies for developing Islamic banking financial inclusion services through Bank Syariah Indonesia (BSI) Agents as extended outlets for reaching underserved communities. Despite Indonesia’s large Muslim population, the outreach and service quality of Islamic banking remain limited compared to conventional banks, driven by human resource constraints, unattractive incentive structures, limited product and service features, aggressive competition from conventional bank agents, and inadequate infrastructure in remote areas. To address these challenges, this study employs the Analytic Network Process (ANP) using a qualitative approach based on expert judgment. Primary data were collected through in-depth interviews with five expert informants comprising academics, BSI practitioners, and regulators. Data collection involved observation, interviews, questionnaires, documentation, and literature review, and the analysis was conducted using the Super Decisions software. Kendall’s Coefficient of Concordance (W) was applied to assess the level of agreement among experts. The results indicate that the most critical constraints are low employee awareness, limited agent competence, unattractive incentive structures, and infrastructure limitations in remote areas. Priority solutions include increasing dedicated human resources for agent management, integrating agent performance into key performance indicators (KPIs), expanding product and service features, and strengthening below-the-line promotion. At the strategic level, the findings highlight the importance of strengthening human resources, developing robust and user-friendly digital agent platforms, and implementing cluster-based agent management. The Kendall’s W values indicate a moderate level of expert agreement, supporting the robustness of the ANP results. This study contributes to the literature on Islamic banking and financial inclusion by providing empirical, strategy-oriented insights into the development of agent-based Islamic banking services. The findings offer practical implications for banks, regulators, and policymakers seeking to strengthen inclusive, sustainable, and competitive Islamic banking ecosystems